The Representation of Major Participants in Bambang Widjojanto’s Arrest in the Jakarta Post Articles: A Critical Discourse Analysis - Arini Ulfia Septiani (Passage, 2015)
This research aims to investigate the major participants in Bambang Widjojanto’s case, how they are represented, and the meanings can be constructed from the representation. The data were taken from five headline news relating to the topic in online newspaper, The Jakarta Post. A Critical Discourse Analysis, especially Van Dijk’s framework, Sociogognitive Approach (2009) focusing on microstructure level has been used to analyze the data. The analysis reveals that there are two major participants in Bambang Widjojanto’s case, Bambang Widjojanto and the Police. The Jakarta Post generally represents Bambang Widjojanto positively, while the Police is represented negatively. Bambang Widjojanto is mostly represented as recipient and the Police is mostly represented as producer, on the other hand. It can be assumed that The Jakarta Post intends to convey that Bambang Widjojanto is a positive recipient or a right/good ‘victim’, while the Police is a negative producer or a wrong/bad ‘actor’. It shows that there is a polarization in representing the participants. This polarization signifies that the Police misused their power over Bambang Widjojanto. Moreover, those representations of the major participants can affect the representation of the institution in which they work.Keywords: The Jakarta Post, representation, CDA, sosicocognitive, microstructure, Bambang Widjojanto